Bioekologi Nyamuk Culex (Diptera: Culicidae) di Kecamatan Jebus Kabupaten Bangka Barat - Atika Rukmana; Eddy Nurtjahya; Awit Suwito (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
Bangka and Belitung region has under 887 collong consisting of 544 under the island of Bangka, and as many as 343 underneath Belitung Island. It has the potential to become a mosquito breeding location in West Bangka, the highest rate of illness with mosquito vector (malaria, DBD, filariasis) is owned by Jebus District. Allegedly this is related to the location of residential communities close to under. The purpose of this research is to know the diversity and bioecology of Culex mosquito in Jebus Subdistrict, West Bangka Regency. This research was conducted in November 2016 - June 2017. This research is an explorative research consisting of several activities, namely: 1) Habitat Observation, 2) Mosquito Sampling, 3) Larvae Maintenance, 4) Mosquito Identification, and 5) Data Analysis . Based on the results of this study found at least 10 types of Culex mosquitoes in Jebus District. Ten types are Cx. nigropunctatus, Culex sp, Cx. quinquefaciatus, Cx. pseudovishnui, Cx. mimulus, Cx. sitiens, Cx. fuscocephala, Cx. hutchinson, Cx. foliatus, Cx. tritaeniorhynchus. The highest relative abundance value in the three species is Cx. quinquefaciatus (0.29%), Cx. nigropunctatus (0.16%), Culex sp. (0.18%). Cx. quinquefasciatus has a blood-sucking peak at 18:00 to 19:00, 20.00.21.00 and 23.00-24.00.